Evaluation of honey authenticity in Thailand by analysis of carbon stable isotope ratio using elemental analyser coupled to isotope ratio mass spectrometry and cavity ring-down spectrometry - Kamdee K. (2023)
In Thailand, honey is used in a variety of commercial products that are distributed in domestic markets and abroad. As honey in Thailand comes from many locations, it is challenging to control the production quality of commercial products. The main problem commonly found in the honey industry is adulteration with undeclared added sugars. Identification of adulterated honey is crucial for authentication, which can increase consumer confidence on honey purity. In this study, 49 honey samples from beekeepers (natural) and 15 commercial honey producers were collected from different cities across Thailand. They were analysed for stable carbon isotope ratios (expressed as 13C/12C or δ13C and reported in relation to the international reference standard unit Vienna Pee Dee Belemnite, ‰ VPDB) using Elemental Analysis Isotope Ratio Mass Spectrometry (EA-IRMS) for developing a δ13C database of natural honey and for checking the adulteration of honey. The δ13C values detected in 49 natural honey samples varied from −23.1‰ to −29.1‰ VPDB with an average of −26.8 ± 1.2‰ VPDB. According to the AOAC standard (No. 998.12, 2019), natural honey should have δ13C values lower than −23.5‰ VPDB, with an acceptable difference in δ13C values between honey and the protein extracted from honey up to 1‰. Compared to the standard guideline, 60% of commercial honey samples collected for this study (9 out of 15 samples) were found to contain undeclared added sugars.